Оценка эффективности влияния низкоинтенсивного лазерного излучения на рост семян редких видов растений - Гурман, Д. В.; Федорцев, Р. В.; Башилов, А. В. (БНТУ, 2025)
The most effective way to stimulate seed growth is to use stimulating laser radiation with λ = 660 nm and optimal irradiation energy in the range from 3.6 to 5.0 J.